Analisis Ring of Security pada Stasiun MRT X - Permana, Aulya; Priyanto, Sapto (UNES Law Review, 2024)
The security of public transportation infrastructure is a crucial aspect in maintaining the stability and continuity of urban society. Mass Rapid Transit (MRT) stations are potential targets for terrorism and other crimes. This study aims to analyze the security of X MRT Station based on the Ring of Security concept. This article, titled "Analysis of the Ring of Security at X MRT Station in Jakarta," uses a descriptive qualitative research method with data collection techniques including field observations and literature studies. The Ring of Security concept is used as an analytical framework to identify weaknesses and strengths in the station's security system. The results show that the station has several strengths, such as robust building design and extensive use of CCTV. However, there are also weaknesses, such as a lack of supervision in certain areas like restrooms and parking lots. Risk analysis and improvement recommendations are proposed to enhance the security of X MRT Station in Jakarta and protect the public from potential terrorism and other crimes. This research contributes to the understanding of public transportation security systems and the importance of implementing a holistic security concept in protecting critical urban infrastructure.